Fostering Green Skills in Vocational Students: The Impact of Learning Environment, Attitudes, and Competence - Azahar, Ridho; Hariyanto, Valentinus Lilik; Prayogo, Wisnu; Fitria, Laili (Universitas Muhammadiyah Surakarta, 2026)
Vocational education plays a crucial role in preparing a workforce that is adaptable to the demands of sustainable development. However, the green skills of vocational school students are still classified as moderate to low, indicating a gap between knowledge and sustainability practices. This research aims to analyse the influence of the learning environment, environmental attitudes, and cognitive competencies on the green skills of vocational school students. The study employs a quantitative approach with a correlational descriptive method, involving 60 students from the construction engineering program selected through simple random sampling. The instrument, in the form of a Likert scale questionnaire, was tested for validity and reliability and analysed using multiple linear regression. The identification results showed that 87% of students have a positive perception of the learning environment, 60% have a good environmental attitude, 22% demonstrate high cognitive competence, and 55% fall into the fairly good category. Statistically, environmental attitude has the most dominant influence (β = .659, p = .000), followed by the learning environment (β = .286, p = .027) and cognitive competence (β = .286, p = .039). The R² value of .761 indicates that the three variables affect students' green skills by 76.1%. These findings imply the importance of transforming vocational learning through the integration of a green curriculum, strengthening sustainable pedagogy, and collaborating with the green industry